Implementasi Hermeneutika Amina Wadud atas Bias “Politik Gender” dalam Syari’at: Rekonstruksi Aurat pada Pria - Suheri Suheri; Robbin Dayyan Yahuda (Asosiasi Ilmu Alqur'an dan Tafsir se-Indonesia, 2019)
Political Gender bias hints at the marginality of women under the control of men. Women seem to never move from the shackles of male dominance in all aspects, not least Syari’at religion. Imam Mazhab organize the woman’s nakedness on all parts of the body except the face, palms and soles of the feet. And the opposite, men strip the body, except between the navel to the knee. Ideal moral distortion is clearly appear at this point, where the prevention of adultery against the fornication is contrary to the facts. Surveys prove that 7 parts of a man’s body which not used in the limits of the genitals, potentialy stimulate women sexual. Thus, the reconstruction of the male aurat is necessary for potential change in Gender Politics bias.This study seeks to launch a new discourse for overcome Gender Political bias in Shari’ah. The study is based on hermeneutics of suspicious that initiated by Amina Wadud as one of the initiators of gender equality. Methods of data analysis are qualitative, referring to previous research results and mixed with other data sources. Three variables are presented in this study: first, the explanation of Amina Wadud’s hermeneutics. Second, the disclosure of gender-bias evidence in Shari’ah. Third, the implementation of Amina Wadud’s Hermeneutic on the Political bias in Shari’ah, which contains the reconstruction offer on the Male aurat. The novelty side of the study lies in the reconstruction of male aurat and the use of Amina Wadud’s Hermeneutic as a blow to the analysis of male problems, where prior research has only focused on women’s issues.